Technological Forecasting : - Wills, Gordon (Pelican Library of buiness and management, 1972)
Discusses some of the reasons young people run away from home, the methods they use to survive away from home, where they can turn for help, and some solutions to the underlying problems. Includes lists by State and city of Travelers Aid locations, hotlines, and halfway houses.